The impact of empowering Saudi women by breaking the glass ceiling on enhancing their role in leadership and entrepreneurship - Zobair, Alwia Saeed Osman; Kodai, Zainab Mohammad Osman; Al-Qahtani, Hanadi yahya maree (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the impact of empowering Saudi women by breaking the glass ceiling on enhancing their role in leadership and entrepreneurship, as the problem of the study was the weak representation of Saudi women in leadership positions contributing to the leadership of creative projects and creativity, which makes looking at the ways one of its capabilities the glass ceiling and enabling it to see the vision 2030 The study adopted the quantitative approach in addition to the historical approach, as the hypothesis of the study was: There is positive a statistical relationship between empowering Saudi women and breaking the glass ceiling and enhancing their role in leadership,entrepreneurship and innovation. The study reached several results, the most important of which are: The study found that there are many factors that have led to the success and effectiveness of women in occupying senior positions and managing projects, the most important of which are: - Saudi women’s self-confidence and skills, while not being afraid of failure, helped them defy difficulties and succeed - Saudi women have the initiative and the technical and humanitarian skills, which have strengthened their role in breaking the glass ceiling. - Saudi women are aware that education is effective in practice (the phrases came first, second, and third, respectively, as is evident from the statistical table. - the study revealed that the study samples approval of the statements ranged between (3.59-4.52) out of table (5) which average between agree and strongly agree respectively. - Table No (3) showed that the arithmetic average of all the responses of sample members amounted to (4.26) indicating that there is strong agreement of statistical significance between empowering Saudi women the glass ceiling and enhancing their role in leadership and entrepreneurship . And based on the results of the study, the study includes many recommendations, the most important of which are We recommend the necessity of conducting studies on Vision 2030 and its impact on the formation of the social structure and trends towards the various economic and social issues that concern Saudi women, due to the necessity of strengthening everyone’s rallying around the vision and supporting it to achieve its goals. Supporting women’s access to leadership positions through the political decision, and gradually raising the share of women from leadership positions, in order to benefit from women’s competencies in developing the development movement in the Kingdom in all fields, We also suggest conducting studies on the reality of empowerment in the private sector and the public sector, because Saudi women occupied leadership positions in the private sector clearly ahead of the public sector, in order to discover and address obstacles to empowerment in the public sector.